Proteomics: a new way to improve human African trypanosomiasis diagnosis?. (June 2013) - Holzmuller, Philippe; Grébaut, Pascal; Semballa, Silla; Gonzatti, Mary Isabel; Geiger, Anne
African trypanosomiases, including the human disease referred to as 'sleeping sickness' and the animal diseases such as nagana, surra and dourine, are neglected vector-borne diseases that after years of research still need improved diagnosis and chemotherapy. Advances in proteomics offer new tools to define biomarkers, whose expression may reflect host–parasite interactions occurring during the infection. In this review, the authors first describe the current diagnostic tools used to detect a trypanosome infection during field surveys, and then discuss their interests, limits and further evolutions. The authors also report on the contribution of molecular diagnostics, and the recent advances and developments that make it suitable for fieldwork. The authors then explore the recent uses of proteomics technology to define host and parasite biomarkers that allow detection of the infection, the power and constraints of the technology. The authors conclude by discussing the urgent need to use the biomarkers discovered in order to develop tools to improve trypanosomiasis control in the near future.